2023
DOI: 10.1017/qpb.2023.13
|View full text |Cite
|
Sign up to set email alerts
|

A blast from the past: Understanding stem cell specification in plant roots using laser ablation

Wouter Smet,
Ikram Blilou

Abstract: In the Arabidopsis root, growth is sustained by the meristem. Signalling from organiser cells, also termed the quiescent centre (QC), is essential for the maintenance and replenishment of the stem cells. Here, we highlight three publications from the founder of the concept of the stem cell niche in Arabidopsis and a pioneer in unravelling regulatory modules governing stem cell specification and maintenance, as well as tissue patterning in the root meristem: Ben Scheres. His research has tremendously impacted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 106 publications
(179 reference statements)
0
2
0
Order By: Relevance
“…In Arabidopsis, the root system architecture comprises primary roots (PRs) and individual lateral roots (LRs) [81]. PRs develop from stem cells surrounding the quiescent center through several rounds of asymmetrical cell divisions and expansions, eventually forming the root meristem [82]. Conversely, LRs originate from the initial specification of pericycle cells, a heterogeneous tissue composed of quiescent cells at the phloem poles and specified cells designated to form lateral root primordia opposite each xylem pole [83].…”
Section: Root Growth and Developmentmentioning
confidence: 99%
“…In Arabidopsis, the root system architecture comprises primary roots (PRs) and individual lateral roots (LRs) [81]. PRs develop from stem cells surrounding the quiescent center through several rounds of asymmetrical cell divisions and expansions, eventually forming the root meristem [82]. Conversely, LRs originate from the initial specification of pericycle cells, a heterogeneous tissue composed of quiescent cells at the phloem poles and specified cells designated to form lateral root primordia opposite each xylem pole [83].…”
Section: Root Growth and Developmentmentioning
confidence: 99%
“…In Arabidopsis research, stem cell and meristematic damages are mimicked by laser ablation of specific, localized cells (Hoermayer et al, 2020;Marhava et al, 2019;Smet & Blilou, 2023;van den Berg et al, 1997), as well as by using drugs like bleomycin that cause programmed cell death (Canher et al, 2020), or hydroxyurea that causes DNA stress (Cruz-Ram ırez et al, 2013). Such experiments have revealed that the regeneration capabilities of the root are not exclusively dependent on the QC.…”
Section: Introductionmentioning
confidence: 99%